Capillary dynamics and the interstitial fluid–lymphatic system. Issue 2 (February 2016) - Waterhouse, Jim; Sawdon, Marina; Kirkman, Emrys
Abstract: The capillaries are the 'business end' of the circulatory system, where materials exchange between the plasma and tissues. Water-soluble molecules can diffuse through pores in the capillaries, and a Gibbs–Donnan equilibrium exists between the plasma and interstitium. There are several types of capillaries, which vary in their anatomical integrity and permeability. There is also a bulk flow of fluids between the plasma and interstitium, described by the Starling forces. Originally, these forces were thought to cause fluids to leave the capillaries at the arteriolar end and return at the venular end; the role of the lymphatics was to provide an 'overflow' mechanism due to protein leakage out of the capillaries. More recent work indicates that this concept needs modification. Lymph flow and interstitial colloidal osmotic pressure are now known to be greater than first thought, and the interstitium has a slightly negative hydrostatic pressure. It is now believed that filtration takes place along most of the capillary, and the lymphatic system plays a more important role in maintaining plasma–interstitium equilibrium and preventing oedema. The system acts as a 'closed' one in that the changes in fluid formation (e.g. following haemorrhage or cardiac failure) are self-limiting. However, in some circulations (e.g. those to the kidneys, glands and the gut), net fluid production or absorption is required. This requirement is fulfilled by an independence from the Starling forces, the systems behaving as 'open' ones.